2019
DOI: 10.1111/cid.12853
|View full text |Cite
|
Sign up to set email alerts
|

Automatic three‐dimensional analysis of bone volume and quality change after maxillary sinus augmentation

Abstract: IntroductionMaxillary sinus augmentation is a widely used surgical procedure to increase the bone volume before implant placement. In order to predict the stability of the implant, analysis of the change in bone volume and quality after a sinus graft procedure is necessary. The purpose of this study was to analyze the change in volume and quality of bone graft material after maxillary sinus augmentation using cone beam computed tomography (CBCT).Methods and MaterialsMaxillary sinus lift procedures using bovine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…measured series of grey values to analyze bone formation in BO grafts. 39 BO granules, however, exhibit a relatively high absorption of X-rays, which is consistent with the present study. Since BO granules and newly formed bone tissue exhibited low contrast in images, the grey values of BO and new bone could only be measured together.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…measured series of grey values to analyze bone formation in BO grafts. 39 BO granules, however, exhibit a relatively high absorption of X-rays, which is consistent with the present study. Since BO granules and newly formed bone tissue exhibited low contrast in images, the grey values of BO and new bone could only be measured together.…”
Section: Discussionsupporting
confidence: 93%
“…Since BO granules and newly formed bone tissue exhibited low contrast in images, the grey values of BO and new bone could only be measured together. 39 However, this procedure needs extensive calculation, which makes it less intuitive in the clinic. In the NS-Sponge group, the mineralization process inside the scaffold was manifested as a gradually extending opaque area in CBCT images, which was different from the high-density radiographs in the BO-Collagen group.…”
Section: Discussionmentioning
confidence: 99%
“…Given this need, the relevance of the use of imaging tests, such as intra and extra-oral radiographs, in addition to cone beam computed tomography, is attested (Kwon, 2019;Giacomini et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The study by Kwon et al (2019) performed the evaluation of 33 patients who underwent surgery to raise the sinus membrane using the transcrestal technique. Six months after the intervention, it was observed that the height of the patients' maxillary sinus varied between 7.88 mm to 21.63 mm, with an average residual bone height of 4.38 mm.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few studies reported graft volume after different types of sinus surgeries. [30][31][32][33] However, this is the first CBCT study in the literature using the current software to investigating the safe volume of the sinus cavity for the grafting. The safe volume after sinus grafting means not to interfere with the osteomeatal unit that hazardous to sinus physiology.…”
Section: Discussionmentioning
confidence: 99%